GIS applications in agriculture. Volume three, Invasive species - Clay, Sharon A. (Sharon Ann) (Boca Raton, FL : CRC Press, 2011)
While many "alien" plant and animal species are purposefully introduced into new areas as ornamentals, livestock, crops, and even pets, these species can escape into other areas and threaten agricultural and native ecosystems causing economic and environmental harm, or harm to human health. Increasingly, scientists are using Geographic Information Systems (GIS) to track and manage the invaders, mitigate the potential rate of spread and level of impact, and protect the native economy and ecosystem. Beginning with an introduction to the use of GIS technology to capture, store, analyze.
ch. 16. Using GIS to investigate weed shifts after two cycles of a corn/soybean rotation / Kurtis D. Reitsma and Sharon A. Clay -- ch. 17. Creating and using weed maps for site-specific management / J. Anita Dille [and others].
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Agricultural pests -- Control -- Data processing; Introduced organisms -- Control -- Data processing; Noxious weeds -- Control -- Data processing; Agricultural informatics; Geographic information systems; Agricultural mapping; Agriculture -- Remote sensing; Electronic books